Penguatan Literasi Digital Dalam Pencegahan Pelanggaran Hukum Siber (Cyber Law) - Suryati, Suryati; Sardana, Layang; Disurya, Ramanata; Putra, Yanuar Syam (Universitas Batanghari Jambi, 2024)
With the advancement of information technology that is increasingly influential, a new legal paradigm has emerged known as cyber law or telematics law. This study aims to understand the role of digital literacy in preventing cyber law violations. The approach to be used in this paper is a normative juridical approach (Legal Research). This approach will be used to analyze various principles and regulations related to Digital Literacy and Cyber Law. This study has specifications as Positive Law Inventory Research. The data used in this study are secondary. The data will be systematically compiled and analyzed in a qualitative normative manner to gain a clear understanding of the issues discussed. The results showed that digital literacy involves attitudes, understanding, and skills in managing and communicating information effectively through various media and formats. With proper strengthening of digital literacy, individuals and organizations can be better prepared to face the challenges of cyber law violations in the digital age.